Plicatura incidental de vena cava inferior - Bogliaccini, Gustavo; Pomi, Jorge; Navarro, Teodoro; Abascal, Winston; Estefan, Alberto; Danza, Rómulo; Praderi, Raúl (Cirugía del Uruguay, 1978)
Increasing incidence of P. T. E. and its importance as death cause in the high-risk-patient group, is analyzed. Case material consists of 8 patients on whom a method of prophylaxis of P. T . E. -incidental plicature of the inferior vena cava- was applied with excellent results. Literature on this method is reviewed.